Backpack palsy: A rare complication of backpack use in children and young adults – A new case report. (September 2016) - Rose, Katy; Davies, Anne; Pitt, Matthew; Ratnasinghe, Didi; D'Argenzio, Luigi
Abstract: Backpack palsy is a well-recognised, albeit rare, complication of carrying backpacks. Although it has been mostly described in cadets during strenuous training, sporadic cases of brachial nerve impairment have been reported in children and young adults. Here we reported the case of a 15-year-old girl who presented with a left-side brachial palsy with axonal denervation of C5C7 motor roots following a school challenge for the Duke of Edinburgh Award. Her symptoms began soon after starting the challenge and included weakness of shoulder abduction and elevation, as well as forearm, wrist and fingers extension. After 6 months of physiotherapy her motor function was completely restored. Backpack palsy can sometimes present in children and young adults. This disorder should be taken in consideration when planning for daily, as well as more challenging, physical activities in these age groups. Highlights: Brachial neuropathy following the use of backpacks is reported in children. Unilateral motor palsy of the upper limbs is the most common presentation. Excellent prognosis is described in about 80% of cases. Avoidance of heavy loads seem to reduce the risk of injury.